Pengaruh Pelayanan dan Harga Jual Terhadap Pendapatan Ekonomi Melalui Penjualan Ayam Pedaging di Kelurahan Olakile Kabupaten Nagekeo - Maria Elviara Tiwe Wanda; Marsel Nande (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2025)
his quantitative study aims to analyze the influence of service quality andselling prices on the economic income of broiler farmers in Olakile Village. Data werecollected via questionnaires and documentation from broiler entrepreneurs. The t-test resultsshow that service has a positive and significant effect on income, indicating that better serviceenhances sales volume. Similarly, the selling price significantly impacts income.Simultaneously, service and price significantly affect income with an value of 0.427, meaningthese variables account for 42.7% of income variation, while 57.3% is influenced by otherfactors such as promotion and product quality. In conclusion, the synergy between service and competitive pricing is vital for farmers' economic stability. The study recommends improvingbusiness management and service quality to optimize profitability.